Pluralism, equality and identity comparative studies - Oommen, T. K. 1937- (New York Oxford University Press, 2002)
With reference to Europe and South Asia.
Includes bibliographical references (p. [174]-181) and indexes.
Keywords: Cultural pluralism -- India; Cultural pluralism -- Europe; Comparative government; National characteristics; Equality